Effectiveness of surgical and combined treatment of supratentorial primitive neuroectodermal tumors in children - Orlov, Yuriy; Shaverskyi, Andrii; Ziabchenko, Vadym; Malysheva, Tatyana; Chernenko, Оksana (Ukrainian Neurosurgical Journal, 2014)
Introduction. The results of use of modern methods of treatment of malignant embryonic brain tumors — supratentorial primitive neuroectodermal tumors (sPNET) are given. Materials and methods. The retrospective analysis of treatment results of 73 children with primitive brain sPNET in a period 1995–2011 was done. Combined methods of treatment were used — surgery, radiotherapy and chemotherapy. Results. The study results demonstrate the need for aggressive therapy at such malignant tumors. After surgery death rate was 5.5%, survival rate in average — 31.2 months. Surgery radicalism, application of radiotherapy and chemotherapy affect the survival rate and quality of life of the patient. Conclusion. Patients older than 3 years at whom according to treatment protocols at sPNEO radiotherapy can be used, as well as a comprehensive approach to treatment are positive predictors of survival and quality of life.